The efficacy of the combination of venetoclax and hypomethylating agents versus HAG agents in patients with acute myeloid leukemia: a retrospective study - Fei Xin; Yan-Hui Yu; Xu-Liang Shen; Guo-Xiang Zhang (Hematology)
Objectives: The purpose of this study was to compare the effectiveness of the combination of venetoclax and hypomethylating agents with the HAG regimen.Methods: We studied 52 cases of newly diagnosed AML and 26 cases of relapsed refractory AML, (including AML patients with treatment-related and ELN-adverse risk disease (n = 50)). These patients were treated with venetoclax and hypomethylating agents and HAG regimens, respectively.Results: Twenty-nine patients newly diagnosed with acute myeloid leukemia were treated with VEN-HMA (venetoclax-hypomethylating agent), while 23 patients were treated with HAG. The median age of the VEN-HMA group was 70 years, while the HAG group had a median age of 69 years. The VEN-HMA group achieved a significantly higher rate of complete remission (82.7%) compared to the cohort treated with the HAG regimen (21.7%) (P < 0.001). At the same time, the VEN-HMA group exhibited a significant survival advantage compared to the HAG treatment group(HR = 0.328, 95%CI: 0.158-0.683, P = 0.003).In patients with relapsed and refractory acute myeloid leukaemia, 43.8% of patients in the VEN-HMA treatment group achieved complete remission, which was similar to the 50% in the HAG treatment group (P > 0.99). The median overall survival was similar between the VEN-HMA and HAG groups, with 4 and 3.67 months, respectively (P = 0.290).Conclusions: In conclusion, our analyses indicated that VEN-HMA resulted in better therapeutic outcomes compared to HAG for newly diagnosed AML patients, with higher rates of complete remission and overall survival. In relapsed/refractory AML patients, there was no significant difference in the efficacy of the two treatments and further studies with larger sample sizes are warranted.